MONTAGE AS SPATIAL RECONSTRUCTION OPERATION METHOD IN DESIGNING CINEMATIC ARCHITECTURE - Neneng Rika Lestari; Kristanti Dewi Paramita; Paramita Atmodiwirjo (MODUL, 2021)
This article investigated montage to understand and arrange cinematic architecture through operations of spatial reconstruction to present a sequence of spatial experiences. Montage is a part of discourses related to cinematic, film, and architecture. This article explored the montage approach as the primary basis in the architectural design process through spatial experience. The discussion is based on the idea that montage is emphasized in three things, i.e., sequence, multiple layers of meaning, and movement. These three aspects were further observed through the montage precedent comprising various cinematic precedents based on montage in architecture, i.e., Manhattan Transcripts and Parc de La Villette from Bernard Tschumi, Villa Savoye from Le Corbusier, and Maison Bordeaux from Rem Koolhaas. The finding of this study is a synthesis of some of these precedents that resulted in an understanding of space reconstruction operations, i.e., dismantlement, disappearance, and reassembly, all three of which exist as strategies that will be part of the production process to develop montage-based cinematic architectural design, creating new spatial sequence that provide alternative spatial experience. This article expands the knowledge regarding montages that cinematics and films can be a development in architectural design.